1994
DOI: 10.1021/ma00100a035
|View full text |Cite
|
Sign up to set email alerts
|

Chain Dynamics of Styrene Polymers Studied by the Fluorescence Depolarization Method

Abstract: The local motion of polystyrenes in dilute solutions was examined by the fluorescence depolarization technique. The samples, polystyrene (PS), poly(a-methylstyrene) (PaMS), and poly(pmethylstyrene) (PpMS), were labeled with the fluorescent probe anthracene in the middle of the main chain. The relaxation time of their local motion in dilute solutions was examined by fluorescence anisotropy measurement. The activation energy of the relaxation time of the polymer chain, E*, was also evaluated by the theory of Kra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 12 publications
1
46
0
Order By: Relevance
“…Pa:MS and PpMS solutions also showed the same tendency; the value of E* in a 0 solvent was 1350 higher above 1 kcal mol -1 than those in good solvents. As described in ref 33, the value of an intrinsic viscosity, i.e., the segment density, changes most steeply near the 0 temperature. In poor solvents, E* is large, because the temperature dependence of the polymeric segment density is larger than that in good solvents.…”
Section: The Activation Energy For Cis-pimentioning
confidence: 63%
See 1 more Smart Citation
“…Pa:MS and PpMS solutions also showed the same tendency; the value of E* in a 0 solvent was 1350 higher above 1 kcal mol -1 than those in good solvents. As described in ref 33, the value of an intrinsic viscosity, i.e., the segment density, changes most steeply near the 0 temperature. In poor solvents, E* is large, because the temperature dependence of the polymeric segment density is larger than that in good solvents.…”
Section: The Activation Energy For Cis-pimentioning
confidence: 63%
“…The value of a~3 corresponds to the reciprocal of chain segmental density, and the dependence of the reduced relaxation time of cis-PI on the segment density was not appreciable. In our previous paper, 33 the reduced relaxation time of polystyrene (PS) became shorter, as the segment density became smaller. The T m/1/ of PS in a 0 solvent, cyclohexane, was 5.4 nscP-1 , and the T m/11 in good solvents, benzene and ethylbenzene, was 2.7nscP-1 and 2.9nscP-1 at 34°C, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…1 -21 For the local motion, which is fairly a fundamental process in chain dynamics, many experimental methods have been utilized, e.g., NMR, 5 -7 ESR, 8 dielectric relaxation, 9 -11 dynamic light scattering, 12 • 13 neutron scattering, 14 and fluorescence depolarization. [15][16][17][18][19][20][21] The fluorescence depolarization method provides direct information about the local motion of polymer chains through a fluorescent probe that is covalently bonded to the polymer main chain. By using this method, we have examined the influence of molecular structure/ 6 · 19 stereoregularity, 17 and quality of solvent16·18 on the chain dynamics of a variety of polymers.…”
mentioning
confidence: 99%
“…16 From the standpoint of the molecular structure, it is interesting to compare the molecular weight effect of PS with that of POE, which is dynamically more flexible than PS. 20 Monnerie et al studied the molecular weight effect of PS on the local motion by NMR, 6 and concluded that the effect of the overall rotational diffusion is negligible on the spin-spin relaxation time of the local motion in a high molecular weight region and that the correlation time remains constant in MW > 10 4 .…”
mentioning
confidence: 99%
“…The relaxation time of the probe was estimated through the measurements of the decay of the fluorescence anisotropy ratio. The local motion of polymer chain has been extensively studied for the polymers with the fluorescent probe labeled in the main chain. We examined the local motion of polymer chains labeled with anthracene as the fluorescent probe in dilute solutions and discussed the effects of several molecular factors such as solvent condition, , molecular structure of polymer, molecular weight, and the position along a chain on the local chain mobility . However, there still remain some questions to be solved.…”
Section: Introductionmentioning
confidence: 99%